Knowledge and Beliefs about Antimicrobial drug resistance and its Implications in Future Prescribers - Chaurasia, Lokeshwar; Sinha, Ragni; Deo, Sushma; Shah, Ram Chandra; Paudel, Gita (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: Antimicrobial drug resistance is the ability of microorganisms to persist or grow in the presence of antimicrobial drugs designed to inhibit or kill them. Since, Bachelor of Medicine and Bachelor of Surgery (MBBS) students will be the future prescribers of antimicrobial drugs, this study aims to observe the existing knowledge and beliefs about antimicrobial drug resistance and its impact on the future use of antimicrobial drugs. Material and Methods: This cross-sectional study was conducted at Janaki Medical College, Janakpurdham, Nepal, among 223 students of Bachelor of Medicine and Bachelor of Surgery (MBBS) program. Data was collected through a structured and customized self administered questionnaire as a tool from the respondents of MBBS first year to MBBS final Year. Chi square test was applied to test the association between different academic years of MBBS and their knowledge on antimicrobial drugs, antimicrobial drug resistance, beliefs about antimicrobial drugs, and implications of the knowledge of antimicrobial drugs and antimicrobial drug resistance. p<0.05 was considered statistically significant. Results: Out of the total participants (n=223), the majority participants were male (n=150) and the mean age of study participants was 22.93±2.15 years. There was no statistically significant difference (p>0.05) in the knowledge on antimicrobial drugs among the different academic years of MBBS. However, there was statistically significant difference (p<0.05) between different academic years of MBBS, in most of the responses related to the knowledge on antimicrobial drug resistance and beliefs on antimicrobial drugs. Most of the students from all the academic years agreed that, their current knowledge of antimicrobial drugs and antimicrobial drug resistance was inadequate, and that they would like to have more education on antimicrobial drugs and antimicrobial drug resistance, for their future career as a doctor. Conclusion: There is a need for more rigorous academic and clinical intervention so that only specific antimicrobial drugs are prescribed with an overall reduction in further development of antimicrobial drug resistance to the existing as well as to the antimicrobial drugs that are still in their clinical trial phases.